Assessment of Shoreline Change Along the Sandy Beach of Ellembelle District of Ghana - Cynthia Borkai Boye; Peter Ekow Baffoe; John Nyamekye Ketibuah (Department of Urban and Regional Planning, Diponegoro University, 2022)
Sandy beaches are most popular tourists and fish landing sites, and serve as habitat for several endangered species. However, sandy beaches more vulnerable to coastal erosion, particularly those along open oceans. Assessment of shoreline change using reliable dataset aid in understanding the morphology of coastal landforms, the processes associated with their occurrence and support decision making. This paper analysed available multi-temporal spatial dataset and field observations using GNSS techniques to assess the shoreline change along the study area. The shoreline features were extracted from 1974 topographic map and 2005 orthophotographs using the High Water Line (HWL) in conjunction with 2020 spatial data. Shoreline change statistics were computed using DSAS. A geodatabase was created, transects were cast and the shoreline change rates computed using EPR, LRR and WLR methods. Both accretion and erosion were recorded with mean erosion rate of 0.97 m/year. It was observed that sections of the shoreline nourished by Ankobra and Amunzuri rivers were experiencing some accretion, particularly the mouth of the Amuzuri river. The estuary of Amunzuri river was found to be drifting eastwards at a rate of 5.4m/year possibly due to tides, waves and currents. The study concludes that in spite of the littoral drift eastwards, fluvial sediment supplied by coastal rivers accounts for the relative stability of shoreline in the area. Policy formulation regarding possible damming of coastal rivers by government under the ‘one district one dam’ agenda must be carefully considered to avert high levels of erosion along the western coast of Ghana.